Thoracic Endovascular Aortic Repair for Penetrating Aortic Ulcer in a Patient with Renal Failure: A Case Report - Bashar, Abul Hasan Muhammad; Kabir, Humayun; Rahman, Mokhlesur; Alam, Md Ahsanul (Cardiovascular Journal, 2021)
Thoracic Endovascular Aortic Repair (TEVAR) is a state-of-the art endovascular intervention used to treat various thoracic aortic pathologies such as aneurysm, dissection and penetrating aortic ulcers (PAU). The procedure demands significant technical skill and involves considerable cost burden for the patients. The latter is the main reason why the procedure has not yet made it to the routine clinical practice in Bangladesh. We recently performed TEVAR for the successful treatment of an ominous-looking PAU in the descending thoracic aorta in a patient with renal failure. Cardiovasc j 2021; 14(1): 88-92